Incomplete airy function - Zhang, Hui (2019)
In this paper, we will be discussing some important properties of the incomplete Airy function - the integral form of the Airy function, its related functions, series expansions, asymptotic expansions and etc.... Furthermore, base on the properties that discussed and obtained, the generalisation of properties are also included as extended applications, and more importantly, it helps us validate our results on our research works.